Method for reducing air hole defect of casting

By introducing ultrafine calcium carbonate, yttrium oxide sand, activated carbon and porous magnesium silicate into the surface and transition layers of the mold shell, the problem of pore defects in titanium alloy investment casting is solved, and the quality of castings is improved.

CN119794258APending Publication Date: 2025-04-11HUNAN LUOLAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510044052.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the precision casting of titanium alloy investment, due to insufficient breathability of the mold shell, pore defects are easily formed in the casting, which affects the quality of the casting.

Method used

The breathability of the mold shell is improved by introducing specific materials into the surface and transition layers of the mold shell. The specific steps include adding ultrafine calcium carbonate and yttrium oxide sand to the top coating, and introducing activated carbon and porous magnesium silicate into the transition layer to absorb the gas generated during casting.

Benefits of technology

It significantly reduces the pore defects of the casting and improves the pass rate of the casting, while not affecting the wet strength, high temperature strength and residual strength of the mold shell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794258A_ABST
    Figure CN119794258A_ABST
Patent Text Reader

Abstract

The invention discloses a method for reducing the air hole defect of a casting, which is characterized in that the air permeability of a surface layer is improved, and a getter material is introduced into a transition layer, so that gas generated during titanium alloy investment casting can be absorbed on the transition layer, the air hole defect of the casting is greatly reduced, and the qualification rate of the casting is remarkably improved. The method is easy to operate, and meanwhile the wet strength, the high-temperature strength and the residual strength of the shell cannot be affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for reducing the porosity defects of castings, belonging to the technical field of investment casting. Background Art

[0002] In investment casting production, the quality of the shell determines the quality of the casting, and the shell is usually required to have:

[0003] 1. Sufficiently high wet strength to prevent shell cracking during transportation or dewaxing;

[0004] 2. High high temperature strength to prevent shell cracking during roasting and casting;

[0005] 3. Low residual strength makes castings easy to clean.

[0006] In addition, the air permeability of the mold shell also has a great influence on the quality of the casting. During the titanium alloy investment casting process, the titanium ingot will absorb some gas before casting, and the gas will overflow during casting. Moreover, titanium is an extremely active chemical element. Liquid titanium reacts chemically with almost all molding materials to varying degrees, and the reaction will also release some gas. If the air permeability of the mold shell is good enough, the gas generated during the titanium alloy investment casting can be discharged in various ways. However, due to the current thickness of the mold shell and the need to use mullite powder sand to solidify layer by layer, it is difficult for the gas to be discharged smoothly from the surface layer to the outside of the mold shell. If the air permeability of the mold shell is not good, the gas will remain in the mold cavity to form pore defects, which seriously affects the quality of the casting.

[0007] Therefore, it is necessary to develop a technical method to prevent the gas generated during titanium alloy investment casting from remaining in the cavity, thereby improving the quality of the casting. Summary of the invention

[0008] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and provide a method for reducing the porosity defects of castings.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] A method for reducing porosity defects in castings, the specific steps are as follows:

[0011] S1. First, yttrium oxide and silica sol are mixed evenly, and ultrafine calcium carbonate is added, stirred evenly, and a surface coating is obtained, and the surface coating is evenly applied to the surface of the wax mold, and yttrium oxide sand is sprinkled to obtain a surface layer of the shell; the surface layer of the shell is evenly coated again to obtain a surface layer of the shell;

[0012] S2. Then add activated carbon, porous magnesium silicate and mullite powder to the silica sol, stir and mix to obtain a transition layer coating, completely immerse the surface of the two-layer shell in the transition layer coating, remove the control material, sand, dry, to obtain a transition layer shell;

[0013] S3. Finally, the transition layer shell is back-coated.

[0014] As one of the preferred technical solutions, in step S1, the particle size distribution of ultrafine calcium carbonate is D90=0.5~1 μm.

[0015] As one of the preferred technical solutions, in step S1, the mass ratio of yttrium oxide to silica sol is 5.3-5.8:1, and the added amount of ultrafine calcium carbonate is 5-8% of the total mass of the surface coating.

[0016] As one of the preferred technical solutions, in step S1, the coating amount of the surface coating on the wax model surface is 0.125 g / cm 2 ~0.155g / cm 2 .

[0017] As one of the preferred technical solutions, in step S1, the amount of yttrium oxide sand is 0.525 g / cm 2 ~0.625g / cm 2 .

[0018] As one of the preferred technical solutions, in step S1, the coating amount of the surface coating evenly coated again is 0.225 g / cm 2 ~0.255g / cm 2 .

[0019] As one of the preferred technical solutions, in step S2, the specific surface area of ​​the activated carbon is 200 to 400 m 2 / g; the particle size of magnesium silicate is D90 = 3-5 μm, and the specific surface area is 300-500 m 2 / g; the particle size of mullite powder is 320 mesh.

[0020] As one of the preferred technical solutions, in step S2, the mass ratio of activated carbon, porous magnesium silicate and mullite powder is 1-2:10-20:10-15.

[0021] As one of the preferred technical solutions, after step S2 is completed, this step is repeated to apply two transition layers.

[0022] As one of the preferred technical solutions, in step S2, the immersion time is 10 to 15 seconds, the material is controlled for 1 to 1.5 minutes, and the coating amount is 0.355 g / cm 2 ~0.455g / cm 2 .

[0023] As one of the preferred technical solutions, in step S2, the sand is mullite sand, and the amount of sand is 0.45 g / cm 2 ~0.55g / cm 2 .

[0024] As one of the preferred technical solutions, in step S2, the drying process conditions are: 22°C ± 2, humidity 55-65%, and drying time 4-8 hours.

[0025] As one of the preferred technical solutions, in step S3, the specific method of back layer coating is: dip the transition layer shell obtained in step S2 into a coating prepared with mullite powder and silica sol, wherein the mullite powder is 320 mesh, the back layer silica sol is 30 silica sol, and the powder-liquid mass ratio is 1.5-4:1, and the viscosity is 18-22S (4# Caien cup test). After fully wetting for 10-15s, it is taken out, sanded, and dried naturally to obtain a back layer 1 shell, wherein the sand is 10-20 mesh mullite sand; the prepared back layer 1 shell repeats the aforementioned dipping, wetting, sanding, and drying steps to obtain a back layer shell or a back layer 2 shell, and the prepared back layer 2 shell repeats the aforementioned dipping, wetting, sanding, and drying steps to obtain a back layer shell; a total of 9 back layers need to be prepared.

[0026] Beneficial effects of the present invention:

[0027] The present invention provides a method for reducing the porosity defects of castings. By improving the air permeability of the surface layer and introducing a gas-absorbing material into the transition layer, the gas generated during titanium alloy investment casting can be absorbed in the transition layer, which greatly reduces the porosity defects of the castings and significantly improves the qualified rate of the castings. The method is simple to operate and does not affect the wet strength, high temperature strength and residual strength of the shell.

[0028] The advantages of the present invention are as follows:

[0029] (1) The present invention introduces ultrafine calcium carbonate into the surface coating. The calcium carbonate undergoes a decomposition reaction at high temperature to generate gas, thereby generating holes in the surface layer. In addition, the calcium oxide produced by the decomposition of calcium carbonate can also react with silicon dioxide in the surface coating to generate calcium silicate, thereby improving the strength and air permeability of the surface layer.

[0030] (2) The present invention introduces a getter material into the transition layer, which can absorb the gas generated during titanium alloy investment casting in the transition layer, greatly reducing the porosity defects of the casting and significantly improving the qualified rate of the casting. The method is simple to operate and does not affect the wet strength, high temperature strength and residual strength of the shell.

[0031] The combined use of these materials in the present invention is difficult. First, the ultrafine calcium carbonate must be surface treated because of its small specific gravity. Otherwise, the ultrafine calcium carbonate will float on the surface of the surface slurry and cannot be well integrated into the slurry. The specific method is to pre-mix the ultrafine calcium carbonate with a wetting agent. The wetting agent is non-ionic and can be fatty alcohol polyoxyethylene ether and fatty alcohol. The mixing ratio is 1000-2000:1-2.

[0032] Secondly, the combination of activated carbon, porous magnesium silicate and 320 mesh mullite powder is also difficult. First, the activated carbon and porous magnesium silicate must be mixed in order to allow the activated carbon to occupy the vacancies of the porous magnesium silicate in advance, thereby leaving pores after calcination. In addition, after the two substances are premixed and added to the silica sol, they must be added after all the 320 mesh mullite powder is added. This prevents a sudden increase in viscosity and agglomeration.

[0033] The invention can greatly reduce the porosity defects of castings, and the porosity of castings is reduced from 10% to 1%, with obvious effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The casting of Example 1 has fewer pores;

[0035] Figure 2 The comparative casting has more pores. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the following description is only for explaining the present invention and does not limit its contents.

[0037] Embodiment 1:

[0038] first step:

[0039] Take 20g of ultrafine calcium carbonate powder with D90=0.5μm, add 0.02g of fatty alcohol polyoxyethylene ether AEO-3 for premixing and set aside. Take 168.25g of yttrium oxide powder and add it to 31.75g ​​of silica sol, with a powder-liquid ratio of 5.3. After stirring evenly, add 10g of premixed ultrafine calcium carbonate powder and continue stirring evenly to obtain a surface coating. Sprinkle the surface coating on the wax model with a coating amount of 0.125g / cm 2 After evenly controlling the material, sprinkle yttrium oxide sand to complete the surface preparation (the amount of yttrium oxide sand is 0.525g / cm 2 Repeat the above steps and apply the slurry prepared in the first step to the wax mold with a coating amount of 0.225 g / cm 2 , complete the preparation of the second layer.

[0040] Step 2:

[0041] Take 20g of specific surface area 200m 2 / g activated carbon, 200g D90 = 3μm, specific surface area 300m 2 / g porous magnesium silicate, add 0.6g ether, 0.2g wetting agent fatty alcohol polyoxyethylene ether AEO-3, and 0.4g magnesium nitrate, pre-mix and set aside.

[0042] Take 100g of 320-mesh mullite powder and add it to 150g of silica sol. After stirring evenly, add 110.6g of the premixed powder to prepare a transition layer coating. The coating viscosity is 18s. Immerse the shell coated with the surface layer in step 1 into the transition layer coating for coating (immersion time 10s). Control the material for 1min and the coating amount is 0.355g / cm 2 , sanding (sanding amount is 0.45g / cm 2 ), and drying (22° C., humidity 55%, drying time 4 hours) to obtain a transition layer shell.

[0043] Repeat this step and apply two transition layers.

[0044] Back layer coating: dip the transition layer shell into the coating prepared by mullite powder and silica sol, wherein the mullite powder is 320 mesh, the back layer silica sol is 30 silica sol, and the powder-liquid mass ratio is 1.5:1, and the viscosity is 18S (4# Caien cup test). Apply and wet it for 10 seconds before taking it out, sprinkling sand, and drying it naturally to obtain a back layer 1 shell, wherein the sand is 10 mesh mullite sand; the prepared back layer 1 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell or a back layer 2 shell, and the prepared back layer 2 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell; a total of 9 back layers need to be prepared.

[0045] The casting obtained by using the shell of Example 1 has fewer pores. Figure 1 .

[0046] Embodiment 2:

[0047] first step:

[0048] Take 32g of ultrafine calcium carbonate powder with D90=1μm, add 0.016g of fatty alcohol polyoxyethylene ether AEO-3 for premixing and set aside. Take 170.59g of yttrium oxide powder and add it to 29.41g of silica sol, with a powder-liquid ratio of 5.8. After stirring evenly, add 16g of premixed ultrafine calcium carbonate powder and continue stirring evenly to obtain a surface coating. Sprinkle the surface coating on the wax model with a coating amount of 0.155g / cm 2 After evenly controlling the material, sprinkle yttrium oxide sand to complete the surface preparation (the amount of yttrium oxide sand is 0.625g / cm 2Repeat the above steps and apply the slurry prepared in the first step to the wax mold with a coating amount of 0.255 g / cm 2 , complete the preparation of the second layer.

[0049] Step 2:

[0050] Take 40g of the specific surface area of ​​400m 2 / g activated carbon, 400g D90 = 5μm, specific surface area 500m 2 / g porous magnesium silicate, add 1.2g ether, 0.4g wetting agent fatty alcohol polyoxyethylene ether AEO-3, and 0.8g magnesium nitrate, pre-mix and set aside.

[0051] Take 300g of 320-mesh mullite powder and add it to 300g of silica sol. After stirring evenly, add 221.2g of the premixed powder to prepare a transition layer coating. The coating viscosity is 22s. The shell coated with the surface layer in step 1 is immersed in the transition layer coating for coating (immersion time 15s). Control the material for 1.5min and the coating amount is 0.455g / cm 2 , sanding (sanding amount is 0.55g / cm 2 ), and drying (22° C., humidity 65%, drying time 8 hours) to obtain a transition layer shell.

[0052] Repeat this step and apply two transition layers.

[0053] Back layer coating: dip the transition layer shell into the coating prepared by mullite powder and silica sol, wherein the mullite powder is 320 mesh, and the back layer silica sol is 30 silica sol, prepared at a powder-liquid mass ratio of 1.5:1, and the viscosity is 22S (4# Caien cup test). Apply and wet it for 10s before taking it out, sprinkling sand, and drying it naturally to obtain a back layer 1 shell, wherein the sand is 20 mesh mullite sand; the prepared back layer 1 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell or a back layer 2 shell, and the prepared back layer 2 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell; a total of 9 back layers need to be prepared.

[0054] Embodiment 3:

[0055] first step:

[0056] Take 24g of ultrafine calcium carbonate powder with D90=0.8μm, add 0.06g of fatty alcohol polyoxyethylene ether AEO-3 for premixing and set aside. Take 169.23g of yttrium oxide powder and add it to 30.77g of silica sol, with a powder-liquid ratio of 5.5. After stirring evenly, add 12g of premixed ultrafine calcium carbonate powder and continue stirring evenly to obtain a surface coating. Sprinkle the surface coating on the wax model with a coating amount of 0.125g / cm 2After evenly controlling the material, sprinkle yttrium oxide sand to complete the surface preparation (the amount of yttrium oxide sand is 0.625g / cm 2 Repeat the above steps and apply the slurry prepared in the first step to the wax mold with a coating amount of 0.225 g / cm 2 , complete the preparation of the second layer.

[0057] Step 2:

[0058] Take 30g of specific surface area 300m 2 / g activated carbon, 300g D90 = 4μm, specific surface area 400m 2 / g porous magnesium silicate, add 0.9g ether, 0.3g wetting agent fatty alcohol polyoxyethylene ether AEO-3, and 0.6g magnesium nitrate, pre-mix and set aside.

[0059] Take 125g of 320-mesh mullite powder and add it to 225g of silica sol. After stirring evenly, add 165.9g of the premixed powder to prepare a transition layer coating. The coating viscosity is 20s. Immerse the shell coated with the surface layer in step 1 into the transition layer coating for coating (immersion time 15s). Control the material for 1min and the coating amount is 0.455g / cm 2 , sanding (sanding amount is 0.45g / cm 2 ), and drying (22° C., humidity 65%, drying time 6 hours) to obtain a transition layer shell.

[0060] Repeat this step and apply two transition layers.

[0061] Back layer coating: dip the transition layer shell into the coating prepared by mullite powder and silica sol, wherein the mullite powder is 320 mesh, and the back layer silica sol is 30 silica sol, prepared at a powder-liquid mass ratio of 4:1, and the viscosity is 18S (4# Caien cup test). Apply and wet it for 15s before taking it out, sprinkling sand, and drying it naturally to obtain a back layer 1 shell, wherein the sand is 10 mesh mullite sand; the prepared back layer 1 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell or a back layer 2 shell, and the prepared back layer 2 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell; a total of 9 back layers need to be prepared.

[0062] Comparative Example

[0063] first step:

[0064] Take 168.25g of yttrium oxide powder and add it to 31.75g ​​of silica sol, with a powder-liquid ratio of 5.3, stir evenly to obtain the surface coating. Sprinkle the surface coating on the wax model with a coating amount of 0.125g / cm 2 After evenly controlling the material, sprinkle yttrium oxide sand to complete the surface preparation (the amount of yttrium oxide sand is 0.525g / cm 2Repeat the above steps and apply the slurry prepared in the first step to the wax mold with a coating amount of 0.225 g / cm 2 , complete the preparation of the second layer.

[0065] Step 2:

[0066] Take 125g of 320-mesh mullite powder and add it to 225g of silica sol. Stir evenly to prepare a transition layer coating. The coating viscosity is 18s. Immerse the shell coated with the surface layer in step 1 into the transition layer coating for coating (immersion time 10s). Control the material for 1min, and the coating amount is 0.355g / cm 2 , sanding (sanding amount is 0.45g / cm 2 ), and drying (22° C., humidity 55%, drying time 4 hours) to obtain a transition layer shell.

[0067] Repeat this step and apply two transition layers.

[0068] Back layer coating: dip the transition layer shell into the coating prepared by mullite powder and silica sol, wherein the mullite powder is 320 mesh, the back layer silica sol is 30 silica sol, and the powder-liquid mass ratio is 1.5:1, and the viscosity is 18S (4# Caien cup test). Apply and wet it for 10 seconds before taking it out, sprinkling sand, and drying it naturally to obtain a back layer 1 shell, wherein the sand is 10 mesh mullite sand; the prepared back layer 1 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell or a back layer 2 shell, and the prepared back layer 2 shell repeats the aforementioned steps of dipping, wetting, sprinkling sand, and drying to obtain a back layer shell; a total of 9 back layers need to be prepared.

[0069] The castings obtained by using the comparative shell have fewer pores, as shown in Figure 2 .

[0070] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A method for reducing porosity defects in castings, characterized in that: The specific steps are as follows: S1. First, yttrium oxide and silica sol are mixed evenly, and ultrafine calcium carbonate is added, stirred evenly, and a surface coating is obtained, and the surface coating is evenly applied to the surface of the wax mold, and yttrium oxide sand is sprinkled to obtain a surface layer of the shell; the surface layer of the shell is evenly coated again to obtain a surface layer of the shell; S2. Then add activated carbon, porous magnesium silicate and mullite powder to the silica sol, stir and mix to obtain a transition layer coating, completely immerse the surface of the two-layer shell in the transition layer coating, remove the control material, sand, dry, to obtain a transition layer shell; S3. Finally, the transition layer shell is back-coated.

2. The method according to claim 1, characterized in that In step S1, the mass ratio of yttrium oxide to silica sol is 5.3-5.8:1, and the added amount of ultrafine calcium carbonate is 5-8% of the total mass of the surface coating.

3. The method according to claim 1, characterized in that In step S1, the coating amount of the surface coating on the wax model surface is 0.125 g / cm 2 ~0.155g / cm 2 ; The dosage of yttrium oxide sand is 0.525g / cm 2 ~0.625g / cm 2 ; The coating amount of the top layer coating evenly applied again is 0.225g / cm 2 ~0.255g / cm 2 .

4. The method according to claim 1, characterized in that: In step S2, the specific surface area of ​​the activated carbon is 200 to 400 m 2 / g; the particle size of magnesium silicate is D90 = 3-5 μm, and the specific surface area is 300-500 m 2 / g; the particle size of mullite powder is 320 mesh.

5. The method according to claim 1, characterized in that In step S2, the mass ratio of activated carbon, porous magnesium silicate and mullite powder is 1-2:10-20:10-15.

6. The method according to claim 1, characterized in that In step S2, the immersion time is 10-15 seconds, the material is controlled for 1-1.5 minutes, and the coating amount is 0.355 g / cm 2 ~0.455g / cm 2 .

7. The method according to claim 1, characterized in that In step S2, the sand is mullite sand, and the amount of sand is 0.45 g / cm 2 ~0.55g / cm 2 .

8. The method according to claim 1, characterized in that In step S2, the drying process conditions are: 22°C ± 2, humidity 55-65%, and drying time 4-8 hours.

9. The method according to claim 1, characterized in that: In step S3, the specific method of back layer coating is: dip the transition layer shell obtained in step S2 into a coating prepared by mullite powder and silica sol, wherein the mullite powder is 320 mesh, the back layer silica sol is 30 silica sol, and the powder-liquid mass ratio is 1.5-4:1, and the viscosity is 18-22S. After fully wetting for 10-15s, it is taken out, sanded, and dried naturally to obtain a back layer 1 shell, wherein the sand is 10-20 mesh mullite sand; the prepared back layer 1 shell repeats the aforementioned dipping, wetting, sanding, and drying steps to obtain a back layer shell or a back layer 2 shell, and the prepared back layer 2 shell repeats the aforementioned dipping, wetting, sanding, and drying steps to obtain a back layer shell; a total of 9 back layers need to be prepared.